Strategi Pembelajaran Baca Tulis Al-Qur’an dalam Menguatkan Aqidah dan Akhlak : Analisis Muatan Lokal di Kota Bogor - Najamudin Najamudin; Dede Dang Sudjana; Dwi Muliati; Ahmad Reza (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
In the midst of the disruption of the digital era and the threat of moral degradation, learning to read and write the Qur'an (BTA) faces major challenges. Currently, BTA is often trapped in cognitive and psychomotor aspects alone—such as reading fluency—but ignores the affective aspect or internalization of spiritual values ​​into the souls of students. This study aims to analyze the BTA learning strategy as a local content subject in its function to strengthen the foundation of students' faith and morals, beyond just the technical ability to read. This study uses a qualitative method with a library research approach. Data were collected through literature analysis related to local content policies, Qur'an teaching methods, and character building theories. The results of the study indicate that an effective BTA learning strategy must integrate three main pillars: A competency-based curriculum and regional potential that emphasizes etiquette. The talaqqi and habituation method that connects the verses of the Qur'an with practical monotheistic values. A holistic approach that positions the Qur'an as a bulwark against extreme thinking and radicalism. This research proposes a reorientation of Quranic reading and writing learning, from merely eradicating Quranic illiteracy to a strategic instrument for strengthening ideology (aqidah) and morality (akhlak) through a local content curriculum that adapts to the challenges of the times. Education policymakers at the regional level are advised to develop BTA curriculum guidelines that focus not only on administrative targets for reading acceptance but also incorporate indicators of character (akhlak) achievement as a primary requirement for graduate competency.